When and why should bone marrow concentrate be used to augment bone integration in osteochondral grafting? - Fortier, Lisa A.; Strauss, Eric J.; Kennedy, John G. (Annals of Joint; Vol 3 (November 2018): Annals of Joint, 2018)
The use of biologics such as bone marrow concentrate (BMC) to augment musculoskeletal tissue repair is promising but simultaneously remains controversial. It is likely that not every patient treated with a biologic such as BMC truly needs it, and vice versa, that not every patient whom could have benefited from BMC receives it. This simple statement indicates that patient selection is critical for application of BMC so that the costs and any morbidity associated with harvest, generation, and application of BMC are only applied in those instances where it is necessary and might improve patient outcomes. Identifying those patients and selecting those cases for which to apply BMC is the nuanced challenge.